FULL ARCH REHABILITATION WITH 4 DENTAL IMPLANTS (CASE REPORT) - Janev, Edvard Jordan; Josifov, Daniel; Janeva, Nadica (Journal of Morphological Sciences; Vol 3 No 3 (2020): JMS, 2020)
Usually, full arch reconstruction of edentulous ridges requires six to ten dental implants. However, some patients demanding fixed implant-supported prostheses are not able to medically or economically afford complex bone grafts or a greater number of implants. These clinical situations could lead the treatment plan toward the all-on-4 protocol. Four dental implant treatment concept offers a reliable solution for patients looking to escape the discomfort that so often comes from wearing a removable denture, or those with a failing dentition who do not want to spend even a day without teeth. Designed to further help clinicians utilize a graftless approach and achieve cortical or bicortical anchorage where bone quality and quantity are limited. Costs for both the doctor and the patient are reduced because less surgical time and fewer products are used. Nevertheless, due to less implant support in this treatment option, mechanical and biological complications might arise.This study describes the treatment of two separate cases a fully edentulous patients, one in maxilla and one in mandibula with fixed implant-supported prostheses on four dental implants. Keywords : Full arch rehabilitation, edentulous jaw, implant-supported dental prosthesis